2018
DOI: 10.1123/jpah.2017-0102
|View full text |Cite
|
Sign up to set email alerts
|

Substituting Sedentary Time With Light and Moderate to Vigorous Physical Activity is Associated With Better Cardiometabolic Health

Abstract: Background: Apply a more novel approach to systematically examine (1) associations of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 27 publications
6
21
0
Order By: Relevance
“…For example, the study by Camhi et al 2013 defined MHO as exhibiting one or fewer cardiometabolic risk factors, while our study stipulated that MHO individuals would not have any of these risk factors 29 . However, our results are supported by other findings showing that reduced sedentary behavior is an independent risk factor for developing cardiometabolic risk factors 10,11 . A systematic review of longitudinal studies on sedentary behavior found that sedentary time was consistently associated with greater risk of all-cause mortality and CVD-related mortality, regardless of PA levels and BMI 11 .…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…For example, the study by Camhi et al 2013 defined MHO as exhibiting one or fewer cardiometabolic risk factors, while our study stipulated that MHO individuals would not have any of these risk factors 29 . However, our results are supported by other findings showing that reduced sedentary behavior is an independent risk factor for developing cardiometabolic risk factors 10,11 . A systematic review of longitudinal studies on sedentary behavior found that sedentary time was consistently associated with greater risk of all-cause mortality and CVD-related mortality, regardless of PA levels and BMI 11 .…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, a recent meta-analysis identified an association between sedentary time and all-cause mortality, independent of PA 11 . These results have been confirmed by other studies, suggesting that high amounts of sedentary time may counteract the benefits of MVPA [10][11][12][13] . Together, these findings point to a need for a more comprehensive evaluation of PA and its relationship with multiple movements and cardiometabolic risk factors.…”
supporting
confidence: 85%
See 2 more Smart Citations
“…Among people with no restless sleep, substituting another type of activity with moderate PA was associated with statistically significantly reduced odds in the presence of bodily pain interference (sleep: adjusted OR ¼ 0. 46…”
Section: Bodily Pain Interferencementioning
confidence: 99%